Optimized UVC-based antifouling system for moored applications - Robert Mars; Bennet Krebs; Mathis Bjoerner; Marialena Christopoulou; Oliver Zielinski (Frontiers in Marine Science)
Biofouling, the unwanted accumulation of marine organisms on submerged structures, significantly compromises the quality of scientific data acquisition. A promising approach to mitigate biofouling on marine sensors is the use of UVC-based antifouling systems. However, existing systems often suffer from low efficiency, leading to high power consumption. This study presents a highly energy-efficient UVC-based antifouling system with a twentyfold increase in energy efficiency compared to previous commercial designs. The system was tested on moored CTDs and fluorometers in the southern Baltic Sea at a depth of 2 meters. Conductivity readings remained within the manufacturer’s specifications for 237 days, demonstrating the effectiveness of the approach in maintaining sensor performance. Based on in-situ measurements in coastal southern Baltic Sea water this study presents a formula to estimate UVC intensity in distances up to 50 cm in order to optimize the settings of UVC-based antifouling systems.